2017
DOI: 10.21134/haaj.v17i2.331
|View full text |Cite
|
Sign up to set email alerts
|

Uso problemático de Internet, el móvil y los videojuegos en una muestra de adolescentes alicantinos

Abstract: ResumenThe intensive use of Information and Communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 46 publications
5
11
0
14
Order By: Relevance
“…In a research conducted in adolescents and young adults people, the consequences of the use of information and communication technologies, including the Internet, cell phones, and video games were assessed. Its results showed that 10% of participants were addicted to all studied technologies, and 2% suffered from two addictions simultaneously (19), which corroborates our findings. In the present study, these results should be due to other factors, such as safety during the game, especially considering that some large cities may have a high rate of theft and related incidents (18).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a research conducted in adolescents and young adults people, the consequences of the use of information and communication technologies, including the Internet, cell phones, and video games were assessed. Its results showed that 10% of participants were addicted to all studied technologies, and 2% suffered from two addictions simultaneously (19), which corroborates our findings. In the present study, these results should be due to other factors, such as safety during the game, especially considering that some large cities may have a high rate of theft and related incidents (18).…”
Section: Discussionsupporting
confidence: 89%
“…Another relevant finding in the present study was that the students who spent more hours playing Pokémon GO had a greater addiction to other video games and made greater use of cell phone applications. Results from other studies have shown an important percentage of students addicted to video games in Peru (17), Colombia (18), Spain (19) and Singapore (20), and addicted to Internet in Peru (21). A research paper published in 2015 found a shorter time used to play video games, which was 10 to 250 minutes in 47% of men and 58% of women (17).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have set the limit of such addiction at about 30 h a week [29]. Bearing in mind that 38.4% of our students spend 35 h a week (five or more hours a day) connected to the Internet (in line with other studies [30][31][32][33]), we could safely say that they have addiction problems and that they may be prone to developing adverse symptoms at physiological, cognitive and behavioral [34][35][36][37] levels.…”
Section: Discussionsupporting
confidence: 64%
“…It is precisely the multiple activities that can be carried out at the same time, that feed two types of needs (social interaction and solitary stimulation), that in turn, feeds the addiction to the Internet. Eighty-five percent of students say they use instant messaging often or very often and 83% use social media and highlight their need to keep in constant contact with their peers [31,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Pero la investigación sobre estas frecuencias elevadas de utilización no solo se ha centrado en Internet, sino también en diversas tecnologías que van desde las Tecnologías de la Información y Comunicación en general (García-Oliva et al, 2017;Gairín y Mercader, 2018) hasta los juegos por Internet (Bertrán y Chamarro, 2016;Martín et al, 2017), videojuegos (Gonzálvez et al, 2015;Espejo et al, 2018), teléfonos móviles (Pedrero et al, 2012;Gaspar y Cuesta, 2015) y, por supuesto, las RSO.…”
Section: Redes Sociales Online Y Adicciónunclassified